Modelling of the viscoelastic behaviour with damage induced anisotropy of a plastic-bonded explosive based on the microplane approach. (15th August 2019) - Chatti, M.; Frachon, A.; Gratton, M.; Caliez, M.; Picart, D.; Hocine, N. Aït
Abstract: In this work, a mechanical constitutive law is proposed for a plastic-bonded explosive (PBX) which is a quasi-brittle energetic aggregate material, submitted to quasi-static loadings. Such material, sensitive to hydrostatic pressure, presents viscoelastic behaviour with damage induced anisotropy and irreversible strains. Previous models developed for this kind of material were mainly devoted for transient dynamic behaviour. The few existing quasi-static models considered the mechanical behaviour either isotropic or only elastoplastic. So, a new viscoelastic Microplane model with the damage induced anisotropy is proposed and implemented in commercial Finite Element software. The viscoelasticity was taken into account using a Maxwell generalized model with Microplane approach. The model consists in implementing the viscoelasticity inside the microplanes defining thus a Maxwell model on every direction. The sensitivity of the model to the strain increment magnitude and to the loading direction was analysed. As main conclusion, the experimental behaviour of the studied material was successfully predicted by this model.